The Capability of the Riau Malay Customary Institution (LAM) in realizing the Riau 2020 Vision - Syed Agung Afandi; Ulung Pribadi (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Riau LAM is a community organization that was present in the midst of the decline in the existence of Malay culture in Riau Province and became the only Malay community organization that was made a partner of the government. This research was conducted in Riau Province in 2018. This study aims to determine the capabilities of Riau LAM in realizing the vision of Riau 2020. The research method used is a qualitative method. The results showed that Riau LAM was unable to carry out planning so that it did not have goals, objectives, and strategies in running the organization. Compilation of organizational structures is not in accordance with existing rules, including the absence of written assignments. Placement of members of the organization is carried out with full interest, the absence of organizational development and oversight functions are ignored. Supporting factors for organizational performance are the possession of financial and physical resources derived from the Riau Provincial Government. The inhibiting factor of organizational performance is not qualified human resources, the lack of cooperation with the Riau Provincial Government, the attitude of the organization is not consistent in dealing with cultural dynamics, and the organization’s bad reputation for performance is not optimal. Thus, it was concluded that Riau LAM did not have the ability to support the government’s performance in realizing the vision of Riau 2020.